Outcome of Mucoid Degeneration of Uterine Fibroid in elderly multigravid woman: A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Mucoid degeneration of uterine fibroids during pregnancy is a rare phenomenon that can pose significant challenges in management. Various form of degenerations may occur in fibroid but myxoid/mucoid denegation is not common. This case report presents a rare instance of Mucoid degeneration of a uterine fibroid in a 40-year-old woman with a history of subfertility. The objective of this report is to highlight the diagnosis and management challenges associated with Mucoid degeneration of fibroids during pregnancy, particularly in women with a history of subfertility. Degeneration may occur in pregnancy though rarest. So, if fibroid is diagnosed in pre- pregnant stage,it must be needed careful monitoring & counselling of patient what happen in pregnancy and how to manage and what treatment modalities are available and what are the outcomes. A detailed case study of the patient’s medical history, clinical presentation, diagnostic procedures, and treatment course is presented. Diagnostic findings, including ultrasound results and laboratory investigations, are discussed. The patient, Jesmin, presented with a history of seeking pregnancy for 4 years, severe dysmenorrhea, and hypothyroidism. Ultrasound revealed a bulky uterus with non-homogeneous myometrium and complex fibroid lesions. By ovulation inducing drug including medication for bacterial vaginosis, Jesmin became pregnant. However, a hypoechoic mass was noted in the posterior wall of the uterus. Cesarean section was performed, and a histopathological examination confirmed leiomyoma with mucoid degeneration. The patient recovered well postoperatively, and both mother and baby were discharged in good health. Mucoid degeneration of uterine fibroids in pregnancy, especially in women with subfertility, requires careful monitoring and management.Bangladesh J Obstet Gynaecol, 2025; Vol. 40(1): 47-51